ANOMALIA EM GÔNADAS DE PARATI Mugil curema VALENCIENNES, 1836. (PISCES - MIGILIDAE) - Eiras, Daura Regina de Brito; Pinoti, Rita (Revista Nerítica, 1986)
Aberrant gonadal development was observed in two females of Mugil curema Valenciennes, 1836 (Mugilidae) collected in Paranaguá Bay (Paraná - Brasil). Collections were taken from november of 1983 to february of 1985, comprising a total of 1020 individuals. This work describes and illustrates the observed malformation.